2015
DOI: 10.1042/bj20150461
|View full text |Cite
|
Sign up to set email alerts
|

Assembly, organization and regulation of cell-surface receptors by lectin–glycan complexes

Abstract: Galectins are a family of β-galactoside-binding lectins carrying at least one consensus sequence in the carbohydrate-recognition domain. Properties of glycosylated ligands, such as N- and O-glycan branching, LacNAc (N-acetyl-lactosamine) content and the balance of α2,3- and α2,6-linked sialic acid dramatically influence galectin binding to a preferential set of counter-receptors. The presentation of specific glycans in galectin-binding partners is also critical, as proper orientation and clustering of oligosac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 138 publications
0
73
0
2
Order By: Relevance
“…As galectin-3 was described to have both extra-and intra-cellular functions (Haudek et al, 2010;Elola et al, 2015) we verified whether addition of soluble recombinant galectin-3 to galectin-3-depleted cells could rescue the observed defect in PDGFRβ endocytosis. As shown in Fig.…”
Section: Cdc42 Is Required For Clathrin-independent Internalization Omentioning
confidence: 97%
“…As galectin-3 was described to have both extra-and intra-cellular functions (Haudek et al, 2010;Elola et al, 2015) we verified whether addition of soluble recombinant galectin-3 to galectin-3-depleted cells could rescue the observed defect in PDGFRβ endocytosis. As shown in Fig.…”
Section: Cdc42 Is Required For Clathrin-independent Internalization Omentioning
confidence: 97%
“…Galectin lattices regulate lateral mobility of integrins (34), junctional stability of N-cadherins (32), receptor distribution at the cell surface (35), turnover of endocytic receptors (33), and intracellular signaling pathways (31,(36)(37)(38). Galectins exhibit a remarkable functional diversity that participates in developmental processes, such as cell differentiation and pathophysiology, (39) cell adhesion and motility, regulation of immune homeostasis, and recognition of glycans on pathogens (26,28,40).…”
Section: +2mentioning
confidence: 99%
“…Galectin binding is influenced by N-glycan branching, LacNAc content and the balance of α2,3-and α2,6-linked terminal Sia (38). While Gal-1 is connected to only α2,3-sialylated poly-LacNAc, Gal-3 is connected to both α2,3-and α2,6-sialylated glycans (109).…”
Section: N-glycan-galectin Latticesmentioning
confidence: 99%
“…Galectin has been shown to function in various biological phenomena such as development, cancer, and immunity, and Galβ1-4GlcNAc is thought to be the major endogenous recognition unit of vertebrate galectins (5)(6)(7)(8). Meanwhile, in recent years, the recognition of exogenous glycans by galectin is also thought to be important for innate immunity (3,6), and it has been shown that galectins have affinities for various disaccharide units that contain β-galactoside structure regardless of whether such disaccharides are found endogenously or exogenously (9).…”
Section: A Introductionmentioning
confidence: 99%